1990
DOI: 10.1021/j100367a085
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical calculations on molecular sieves. 2. Model cluster investigation of silicoaluminophosphates

Abstract: Ab initio molecular orbital calculations have been performed on model clusters simulating silicate, aluminosilicate, and silicoaluminophosphate dimeric and trimeric entities. This investigation was aimed at obtaining preliminary information on the relative stability of the Si-O-AI, Si-0-P, and AI-0-P bridges and on modifications generated by the presence of phosphorus in such and related systems. The results show that the AI-O-P bridge is more stable than Si-0-AI or Si-0-P linkages, which is in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…It suggests that increasing the amount of water in the reactive mixture leads to the presence of more physisorbed water, however it does not seem to (1206 cm -1 ), its relative intensity diminishes when (nP/nAl) + nH2O increases. This can be explained by the preferential formation of aluminophosphate entities [38], when the species are available. Besides, for higher Al/P ratios, the presence of large amounts of unreacted metakaolin and undissolved silica is higher, and the molecular interactions will thus favor the formation of Si-O-P and Si-O-Al bonds [39].…”
Section: Discussion: Modification Of the Networkmentioning
confidence: 99%
“…It suggests that increasing the amount of water in the reactive mixture leads to the presence of more physisorbed water, however it does not seem to (1206 cm -1 ), its relative intensity diminishes when (nP/nAl) + nH2O increases. This can be explained by the preferential formation of aluminophosphate entities [38], when the species are available. Besides, for higher Al/P ratios, the presence of large amounts of unreacted metakaolin and undissolved silica is higher, and the molecular interactions will thus favor the formation of Si-O-P and Si-O-Al bonds [39].…”
Section: Discussion: Modification Of the Networkmentioning
confidence: 99%
“…The last phase transition was the formation of mullite from residual, fully dehydroxylated MK particles at 980 to 1010 ºC [44], and is especially prominent in the raw MK particles. For all geopolymer samples, such a peak is less significant, indicating that the raw MK particles had reacted with the phosphate activating solution to synthesize new gels: silico-alumino-phosphate (S-A-P) gel [16] and amorphous or semi-crystalline aluminum phosphate compounds [12,17].…”
Section: Thermogravimetrymentioning
confidence: 99%
“…This reaction occurs in an acidic or low-alkaline medium environment in which a phosphate or phosphoric acid solution, rather than the alkali-silicate used in conventional geopolymers, chemically activates the aluminosilicate precursors to yield a compact geopolymer matrix with a condensed structure of silico-alumino-phosphate linkages [14,15]. It has been claimed that the newly formed Al-O-P linkages could balance the charge caused by changes in the chemical environment of aluminum [16], as is also observed in the synthesis of charge-neutral crystalline zeolite-like aluminophosphate and silico-alumino-phosphate frameworks [17]. Thus, a charge balance within the molecular structure is achieved without the involvement of monovalent cations.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment comes from the fact that a diffuse basis function located on an atom may to some extent cover the regions of the other adjacent atoms leading to overestimating the population of this atom slightly in the Mulliken population analysis. Derouane and his coworkers showed that the partial charges calculated by the 6‐21G basis set are higher than those obtained from the STO‐3G basis set, and thus, STO‐3G charges may be more reliable. Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets.…”
Section: Computational Detailsmentioning
confidence: 99%